2018
DOI: 10.1007/s12035-018-1252-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Brain Networks Underlying Alcohol Binge Drinking Using a Systems Genomics Approach

Abstract: Alcohol use disorder (AUD) is a complex psychiatric disorder with strong genetic and environmental risk factors. We studied the molecular perturbations underlying risky drinking behavior by measuring transcriptome changes across the neurocircuitry of addiction in a genetic mouse model of binge drinking. Sixteen generations of selective breeding for high blood alcohol levels after a binge drinking session produced global changes in brain gene expression in alcohol-naïve High Drinking in the Dark (HDID-1) mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 67 publications
0
38
0
Order By: Relevance
“…Starting with a genetically heterogeneous progenitor stock (HS/NPT), selective breeding was carried out to create 2 unique High Drinking in the Dark (HDID‐1, HDID‐2) mouse lines that represent models of genetic risk for binge‐like drinking (Crabbe et al, ; Crabbe et al, ). HDID and HS/NPT mice have been extensively characterized (Barkley‐Levenson and Crabbe, ; Barkley‐Levenson and Crabbe, ; Barkley‐Levenson and Crabbe, ; Barkley‐Levenson and Crabbe, ; Barkley‐Levenson et al, ; Barkley‐Levenson et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Ferguson et al, ; Ferguson et al, ; Fritz et al, ; Iancu et al, ; Iancu et al, ; Metten et al, ). Of particular relevance to the current studies are the findings that HDID mice exhibit behavioral impairment after DID (Crabbe et al, ), withdrawal after a single binge‐drinking session (Crabbe et al, ), and do not exhibit altered preference for saccharin or avoidance of quinine solutions (Crabbe et al, ) or alcohol clearance rates (Crabbe et al, ).…”
mentioning
confidence: 99%
“…Starting with a genetically heterogeneous progenitor stock (HS/NPT), selective breeding was carried out to create 2 unique High Drinking in the Dark (HDID‐1, HDID‐2) mouse lines that represent models of genetic risk for binge‐like drinking (Crabbe et al, ; Crabbe et al, ). HDID and HS/NPT mice have been extensively characterized (Barkley‐Levenson and Crabbe, ; Barkley‐Levenson and Crabbe, ; Barkley‐Levenson and Crabbe, ; Barkley‐Levenson and Crabbe, ; Barkley‐Levenson et al, ; Barkley‐Levenson et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Ferguson et al, ; Ferguson et al, ; Fritz et al, ; Iancu et al, ; Iancu et al, ; Metten et al, ). Of particular relevance to the current studies are the findings that HDID mice exhibit behavioral impairment after DID (Crabbe et al, ), withdrawal after a single binge‐drinking session (Crabbe et al, ), and do not exhibit altered preference for saccharin or avoidance of quinine solutions (Crabbe et al, ) or alcohol clearance rates (Crabbe et al, ).…”
mentioning
confidence: 99%
“…Furthermore, Ferguson et al (2019) found many changes in brain gene expression between ethanol-naïve HDID-1 and HS/Npt mice, specifically in glutamatergic and GABAergic signaling pathways in the NAc (shell) [59]. The brain regions used in Ferguson et al (2019) represent circuitry well known to be involved in motivated behaviors, as well as alcohol drinking [59]. Hdac4 was identified in selection responsive modules as functionally overrepresented.…”
Section: Effects Of Chronic Binge-drinking and Dreadds On The Nac Tramentioning
confidence: 99%
“… 5 Both HDID lines display marked differences in brain gene co-expression patterns compared to HS/NPT. 6 - 8 Compared to HDID-2, HDID-1 are further along in selection and maintain a much greater genetic distance from that of C57BL/6J, of which many of the chosen pharmacotherapies have already been tested. 6 Therefore, the following work caters to the unique genetic diversity of HDID-1.…”
Section: Introductionmentioning
confidence: 99%